Is There Still Son Preference in the United States? - Francine D. Blau; Lawrence M. Kahn; Peter Brummund; Jason Cook; Miriam Larson-Koester (Institute of Labor Economics (IZA), 2017)
In this paper, we use 2008-2013 American Community Survey data to update and further probe Dahl and Moretti's (2008) son preference results, which found evidence that having a female first child increased the probability of single female headship and raised fertility. In light of the substantial increase in immigration, we examine this question separately for immigrants and natives. Among the population in the aggregate, as well as among the native-born separately, consistent with Dahl and Moretti (2008), we find that having a female first child raises the likelihood that the mother is a single parent. However, in sharp contrast to Dahl and Moretti (2008), we find that having a female first child is actually associated with lower fertility. Thus, by the 2008-2013 period, any apparent son preference among natives in their fertility decisions appears to be outweighed by factors such as cost concerns in raising girls. This change may be plausible in light of the reversal of the gender gap in college attendance beginning in the 1980s (Goldin, Katz and Kuziemko 2006), making girls more costly. For immigrants, we also find evidence that having a female first child contributes to female headship, with an effect that has the same magnitude as that for natives although is not statistically significant. However, in contrast to natives, we do find a positive fertility effect, suggesting son preference in fertility among this group. This interpretation is further supported by evidence that, for both first and second generation immigrants (second generation immigrants were examined using the Current Population Surveys) having a girl has a more positive effect on fertility for those whose source countries have lower values of the World Economic Forum's Gender Equity Index, or lower female labor force participation rates and higher sex (boy-to-girl) ratios among births. We also examine sex selection and find no evidence that sex selection has spread beyond the race groups identified in previous work (e.g., Almond and Edlund 2008).
Keywords: J1; J11; J12; J13; J15; J16; 330; gender; son preference; family structure; fertility; sex selection; immigrants